Association between tennis training experience and executive function in children aged 8–12 - Xu, Yue; Zhang, Wanxia; Zhang, Hanfeng; Wang, Lijuan; Luo, Yanlin; Ni, Guoxin (Frontiers in Human Neuroscience, 2022)
Cognitively engaging activities have been shown to facilitate the improvement of executive functions in children. However, a limited number of studies have investigated the relationship between dose parameters of physical activities and executive functions, and heterogeneity exists. In the present study, we aim to explore the association between tennis training experience and executive functions in children. Sixty children aged 8-12 years were recruited in this study and were allocated to the short-term (ST) group (less than 12 months, n=30) and the long-term (LT) group (more than 12 months, n=30). The abilities of inhibitory control, cognitive flexibility, and working memory were measured by the Stop-signal task, Switching task, and N-back task respectively. There was no significant group difference in either the accuracy or reaction time of the Stop-signal task. No significant difference between groups of the accuracy in the Switching task was observed. However, LT group presented a shorter reaction time than the ST group (731.69±149.23ms vs. 857.15±157.99ms, P<0.01) in the Switching task. Additionally, training experience was positively associated with the reaction time of the Switching task. As for the N-back task, in comparison with the LT group, the ST group showed a longer reaction time (711.37±168.14ms vs. 164.75±635.88ms, P<0.05). Moreover, training experience was also positively associated with the reaction time of the N-back task. But there was no significant group difference in the accuracy of the N-back task. In conclusion, children trained for over one year have better performance in cognitive flexibility and working memory than those trained in less than one year. And tennis experience is positively associated with executive functions.